Numerical analysis of influence of length of the working part of specimen on dynamic diagrams of constructional materials obtained by the Kolsky method - Konstantinov Alexander Yu.; Basalin Artem V.; Gonov Mikhail E.; Filippov Andrey R. (MATEC Web of Conferences, 2018)
It is known that experiments with intensive dynamic influences and high-speed deformation of specimens under tension are important in the analysis of deformations and strength of structures and their elements. The most reasonable and widely used method for obtaining dynamic stressstrain curves, characteristics of ultimate strength and deformations is the modified Kolsky method. It should be noted a small number of publications on the analysis of the influence of fillets and the length of the working part of the specimen on the most important mechanical characteristics obtained by this method. This work is aimed at increasing knowledge in this area. By numerical and experimental analysis it was established that when the working part of the specimen has a length of 5 mm, then the uniformity and one-dimensionality of the stressed state are seriously violated. When choosing the length of the specimen in the Kolsky method, there are important limitations: the length of the specimen must be much smaller than the length of the loading pulse. Therefore, in this study, two specimen lengths of 10 and 15 mm were analyzed. In this paper, we give experimental and calculated diagrams and their comparison with each other. It was shown, that for the above-mentioned lengths, the homogeneity and one-dimensionality of the stressed state is substantially improved.